The dynamical admittance spectrometer: Instrument development and its application to chemical kinetics. (June 2016) - Xu, Hui; Rong, Zhou; Tang, Chao; Liu, Xia; Shen, Yin; Dou, Guo-Sheng; Liu, Rui-Lan; Jiang, Bing; Fan, Qu-Li; Huang, Wei
Highlights: Dynamical admittance spectrometer was developed. It was based on the virtual instrument and infinitesimal principle. The chemical kinetics could be easily researched. Abstract: According to the intrinsic characteristics of the admittance spectrum, its application to kinetic research possesses some advantages. So in this report, based on the virtual instrument technology and infinitesimal principle, one dynamic admittance spectrometer was developed and primarily applied to the research of chemical kinetics. The hardware configuration mainly included five parts: signal generator, chemical system container, amplification circuit, data collecting circuit, the host computer and its application program. In order to realize the real-time dynamical test, two methods could be adopted, which were frequency response and time response (namely impulse response). It could be seen that the two methods were almost same for the chemical reaction system in this report. When the instrument was established, the measurement error of the instrument was tested through the matured commercial electrochemical workstation. It could be easily found that our dynamical spectrometer was better than the electrochemical workstation. Because the chemical reaction was continuous changing system, the infinitesimal principle was used to dynamical measurement. For the sucrose hydrolyzation system under acid, the time length for one infinitesimal was determined to be one second by experiments. Thanks to the characteristics of admittance, the catalyst hydrochloric acid was highly conducting and with little capacitance value, but the other reactants are highly insulating and with little conductance value. So when measuring capacitance value to represent the concentration of the reactants, the testing error can be ignored. Then the standard capacitance–concentration curve could be obtained. From the dynamically testing results and the standard capacitance–concentration curve, the function relationship between concentration of sucrose and reaction time could be obtained. At last, the kinetic equation of hydrolyzation of sucrose under HCl could be determined to be r = - d [ sucrose ] dt = kc SU 1 c HCl 1.46, with total reacting order of 2.46.